(untitled) (Docentes 2.0 Journal, 2021)
The upswing that technologies have reached is influencing the entire panorama of people’s productivity and social work. All this from an economic and scientific development perspective, promoting a range of opportunities to transform social and productive dynamism, in other words, from an economic conception. Hence, this study’s objectives were to establish a theoretical conception about digital empowerment and the sustainable development of the business sector. Likewise, it was oriented to determine the relationship between digital empowerment and the sustainable development of Colombia’s business sector. Therefore, it was established in a positivist methodology, typified as analytical - descriptive, and correlational; the sample consisted of 32 university teachers and 22 students who have ventured into the labor sector. The information was collected through a structured questionnaire with multiple response alternatives. The results showed regarding the first objective that the conception of digital empowerment is weak, assumed as the use of ICT. Regarding the second objective, a correlation of 0.763 was evidenced at a significance level of 0.033, indicating a high and statistically significant relationship between the variables.